PRELIMINARY STUDY OF EMOTIONAL INTELLIGENCE AND COMMUNICATION SATISFACTION ON JOB PERFORMANCE: A STUDY ON MALAYSIAN HOTEL INDUSTRY - Mohd Tahir, Izah; Monil, Muzalifah (Journal of Human Capital Development (JHCD), 2015)
Employees job performance of frontline employees in hotel industry are becoming more important as they provide a benchmark for the hotel industry to excel in terms of the quality of services provided. This study aims to examine the effect of emotional intelligence and communication satisfaction on job performance using causal steps approach. A structured questionnaires consisting of job performance (18 items), emotional intelligence (21 items) and communication satisfaction (17 items) were adapted from previous research. 102 respondents from the frontline employees were chosen from selected star rating hotel in Malaysia. The results indicate that emotional intelligence and communication satisfaction are significant and positively correlated with job performance. The partial mediator occurs from the model and these results could be used by the hotel industry to perform transfer of training to increase frontline employee’s performances. Keywords: emotional intelligence, communication satisfaction, job performance, mediation, hotel industry